Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1039/b301141k
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bond forming ionophore for highly efficient transport of phosphate anions across the nitrobenzene–water interface

Abstract: Thiourea-based hydrogen-bond forming ionophore 2, alpha,alpha'-bis(N'-p-nitrophenylthioureylene)-m-xylene, is synthesized and investigated by using ion transfer polarography for the facilitated transfers of H2PO4-, HPO42- and Cl- across the nitrobenzene-water interface. Bis-thiourea 2 has a significant ability to assist H2PO4- transfer across the interface whereas its counterpart, N-(p-nitrophenyl)-N'-propylthiourea (ionophore 3), cannot facilitate the transfer of this hydrophilic anion. The H2PO4- transfer as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…This interaction would be similar to that described, based on studies concerning the structure-activity relationships, between hydroxyl groups in sweet-tasting sugars and the human sweet taste receptor [32]. In fact, literature [29,32,48,49] reports that the electric response of potentiometric E-tongue to sugars may be due to the interaction on the surface of the lipid/polymer membrane (at the oil/water interface), either derived from the establishment of hydrogen bonds or due to the presence of some mediating electrolyte substances, between carboxyl or phosphate groups in the lipid/polymer membrane and the two vicinal hydroxyl groups of the sugar molecules. The response of the potentiometric E-tongue towards the organic acids present in the fruit beverages, may be explained since these molecules, which are electrolytes, electrically interact with the lipid/polymer membrane and after being adsorbed induce a change in the membrane potential [30,31].…”
Section: E-tongue Signals Profiles Of Beverage Samplessupporting
confidence: 77%
“…This interaction would be similar to that described, based on studies concerning the structure-activity relationships, between hydroxyl groups in sweet-tasting sugars and the human sweet taste receptor [32]. In fact, literature [29,32,48,49] reports that the electric response of potentiometric E-tongue to sugars may be due to the interaction on the surface of the lipid/polymer membrane (at the oil/water interface), either derived from the establishment of hydrogen bonds or due to the presence of some mediating electrolyte substances, between carboxyl or phosphate groups in the lipid/polymer membrane and the two vicinal hydroxyl groups of the sugar molecules. The response of the potentiometric E-tongue towards the organic acids present in the fruit beverages, may be explained since these molecules, which are electrolytes, electrically interact with the lipid/polymer membrane and after being adsorbed induce a change in the membrane potential [30,31].…”
Section: E-tongue Signals Profiles Of Beverage Samplessupporting
confidence: 77%
“…Moreover, it seems that this interaction itself must occur on the surface of the lipid/polymer membrane of the sweetness sensor, that is, oil/water interface, like in the other examples reported. (13,14) However, even if such an interaction itself may be possible there, the reason why an electric potential change is observed in the sweetness sensor from sugars, which are nonelectrolytes, is still unknown. On the other hand, if the interaction is indirect, then, there may be some mediating substances between the carboxyl group and the two vicinal hydroxyl groups.…”
Section: Interaction Between Sweetness Sensor and Sugarsmentioning
confidence: 99%
“…The assisted transfer of phosphate at water/DCE interfaces employing a bis-urea-calix [4]arene [80] as receptor was reported, together with a similar study at water/NB interfaces with a bis-thiourea ligand. [81] Shao et al [82] reported the facilitated ion transfer of four anions (NO2 -, Cl -, Br -and COO -) facilitated by calix-pyrrole ligands at a micro-interface, while Dryfe and colleagues [83] reported the transfers of a series of anions facilitated by a cholapod ionophore, and determined their complexation constants.…”
Section: Facilitated Ion-transfer (Fit) Reactionsmentioning
confidence: 99%